Technology for Facial Expression Recognition Across Different Scenes - Zhang, Hongrui (Exploring Science Academic Conference Series, 2026)
This paper conducts a systematic review and analysis of the key technologies for facial expression recognition across different scenarios. As the facial expression recognition technology moves from the laboratory to diverse real -world scenarios such as remote healthcare, mental health , and intelligent cabins, ensuring the model maintains high performance in complex environments has become a core issue that needs to be urgently addressed. Firstly, this paper reviews three key technology systems focusing on environmental robustness, efficient deployment, and data scarcity and domain adaptation. It elaborates on representative methods such as attention mechanisms, lightweight networks, and domain adaptation, along with their progress. Based on this, it further analyzes the common challenge s faced in cross -scenario applications, including environmental interference, data distribution differences, and deployment constraints. The review results indicate that there is no universal optimal model. The technical solutions need to be deeply adapted to specific scene requirements. The integration of robustness, lightweighting, and domain adaptation technologies is the future development trend. This paper provides theoretical basis and practical references for the selection of facial expression recognition technologies for specific scenarios.